IMPLEMENTATION OF TIK IN IMPROVING INDONESIAN LEARNING OUTCOMES FOR STUDENTS OF SMAN 16 MAKASSAR - Restu Dinda; Sitti Rabiah; Nurmiah Muin (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The use of technology has a very positive effect on the process of imparting knowledge in education. The use of good information and communication technology is able to play an active role in providing assistance in the field of education. The purpose of this study is to improve student learning outcomes in learning Indonesian through the application of ICT. The method used is classroom action research in a collaborative form, where researchers are directly involved in the research process from the beginning to the end of the research. The results of this study were an increase in student learning outcomes of SMAN 16 Makassar in each cycle, namely in the pre-cycle in class X MIPA 3 as many as 2 people reached the KKM, in cycle 1 as many as 15 people, and cycle 2 as many as 34 people. In class XI MIPA 2 at the pre-cycle stage no one reached the KKM, Cycle 1 as many as 18 people, and cycle 2 as many as 33. Furthermore, in class XII IPS 1 in the pre-cycle stage there were 2 students who reached KKM, cycle 1 as many as 13 people. , and cycle 2 as many as 28 students. The results of this study indicate that the application of ICT in SMA Negeri 16 Makassar can improve student learning outcomes in learning Indonesian.